Hashtag activism: Analysing linking discourse markers in #ArewaMeToo conversations on X platform - Chimuanya, Lily; Uyah, Uduak-Abasi (Masyarakat, Kebudayaan dan Politik, 2025)
Hashtag activism has emerged as a powerful tool for online advocacy, enabling marginalized individuals to gain visibility and foster collective action. In the absence of physical cues, users rely on linguistic elements to express engagement and support through linking discourse markers. Therefore, the subject of this study focuses on how connecting discourse markers are used in the #ArewaMeToo online conversation to express stance and inclusivity, on sexual violence. The study also explores how discourse markers function as substitutes for physical conversational cues in online activism. The study was conducted in 2024 using a qualitative method. Data were purposively selected from #ArewaMeToo conversations on X platform in Nigeria and grouped through discourse analysis. The database was collected from 300 tweets, with 63 tweets selected for analysis and reproduced in this study as representative examples. The findings of the study revealed that the discourse markers employed in the #ArewaMeToo movement such as cohesive devices, punctuation and capitalization have emerged as crucial tools for conveying engagement, support, emotional intensity and reinforcing advocacy. The study concludes that linking discourse markers substitute for vocal differences and serve as linguistic resources that signal solidarity, emotion, and resistance in the fight against sexual violence.